A novel WTX mutation in a female patient with osteopathia striata with cranial sclerosis and hepatoblastoma. Issue 4 (23rd January 2014) - Fujita, Atsushi; Ochi, Nobuhiko; Fujimaki, Hidehiko; Muramatsu, Hideki; Takahashi, Yoshiyuki; Natsume, Jun; Kojima, Seiji; Nakashima, Mitsuko; Tsurusaki, Yoshinori; Saitsu, Hirotomo; Matsumoto, Naomichi; Miyake, Noriko
<x xml:space="preserve">Abstract</x> Osteopathia striata with cranial sclerosis (OSCS) is an X‐linked dominant sclerosing bone dysplasia. Typically affected females show macrocephaly, characteristic facial appearance, cleft palate, mild learning difficulties, hearing loss, sclerosis of the long bones and skull, and longitudinal striations visible on radiographs of the long bones, pelvis and scapulae. Typically affected males usually die at the fetal or early neonatal stage. Because of its variable expressivity, which ranges from asymptomatic to fetal death, clinical diagnosis of OSCS can be difficult. Here, we identify a unique female patient presenting with severe macrocephaly, characteristic facial appearance, developmental delay, and hepatoblastoma. Exome sequencing identified a novel de novo nonsense mutation (c.1045C>T, p.Glu349*) in the WTX gene associated with OSCS. The OSCS diagnosis was confirmed in this patient based on the hallmark appearance of longitudinal striations in long bones when viewed by X‐ray. WTX is also known as a tumor suppressor gene, and somatic mutations in that gene have been identified in Wilms tumors. In addition to this patient, although two patients with OSCS have been reported to have colorectal cancer or ovarian cancer, Wilms tumor has never been reported in association with this disorder. Tumor susceptibility in patients with OSCS is discussed. © 2014 Wiley Periodicals, Inc.